INFLUENCE OF IFAD RICE VCDP ON ACCESS TO MARKET AMONG RICE FARMERS IN SOUTHEAST NIGERIA - Samuel, J.E.; Tijani, S. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
This study examined the influence of IFAD rice VCDP on access to market among rice farmers in Southeast, Nigeria. A multi-staged sampling technique was deployed to 318 respondents from the study area. Data were collected using structured questionnaires. The data were subjected to both descriptive (mean and percentages) and inferential (t-test) statistics. The results showed that the mean age of the respondents was 43.11±8.32 years and majority (81.4%) were within the age range of <31-50 years, almost two-thirds (61.9%) were male and majority (86.70%) were literate at different levels. Also it showed that the mean total farm income was 1490455.97±1250913.3 and almost half (46.6%) of the respondents had <1,000,000 as their total farm income, with a mean farm experience of 2.08±0.29 years. In the same vein, majority (87.2%) of the respondents cultivated the raining season rice, with the mean average rice yields of 4843.40±969.60, and more than half (56%) had average rice yield of 4-5tonnes/ha and majority (57.1%) employed hired labour . Furthermore, majority (85.0%) of the respondents had a low level of benefit derived from rice farming prior to the intervention but as a result of the intervention, 77.2% of the respondents had high level of benefit derived with a mean of 20.90±1.72. In the same vein, before the intervention, majority (78.6%) of the respondents had low access to market, however, as a result of the intervention, most (90.8%) had high access to market with a mean of 6.35±4.61. And finally, it was shown that there was a significant difference in farmers’ access to market before (1.9±1.0) and after (10.8±1.3) IFAD rice VCDP intervention in the study area p≤0.05. The study concludes that IFAD rice value chain development programme has significantly influenced market access among beneficiaries in the study area. The study recommends that this programme be sustainable, so that these benefits derived by the beneficiaries will never be short-leaved. The study also recommends that a functional off-takers be made available to the farmers to ensure a sustainable access to market.